(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The Study aimed to identify the role of strategic management in improving the level of institutional performance in the governmental university colleges in the southern governorates. The study uses descriptive analytical method and questionnaire as a data collection tool. The study includes all the staff in the governmental university colleges except service employees who are (435) ones. The study used the random stratified sample method according to the college. (240) questionnaires were distributed, (205) responses were retrieved (89.13%). The study found a statistically significant relationship at the level of (a≤0.05) between strategic management and institutional performance in the governmental university colleges in the southern governorates and there is a statistically significant effect at the level of (a≤0.05) between strategic management and institutional performance in the governmental university colleges. The study also reached a number of recommendations, the most important of which is the need to increase attention to strategic management and its stages; because of their direct impact on improving the level of institutional performance in government colleges, and the need for university colleges to useconsultants specialized in the analysis and assessment of environmental variables, and to invest in the capabilities of the potential and potential to ensure the improvement of institutional performance.